Exclusively intertubular seminoma arising in undescended testes: Report of two cases - Ying-Hsia Chu; Wei Huang; Rong Hu (Elsevier, 2018)
Exclusively intertubular seminoma is a rare and easily overlooked variant that often poses diagnostic challenge. It is characterized by the absence of grossly apparent tumor and tumor cells dispersed in the intertubular space without forming an expansile lesion microscopically. We herein report two such cases, both arising in undescended testes in adult patients. The goal is to highlight this potential diagnostic caveat in examining orchiectomies performed for cryptorchidism in adult patients. Keywords: Undescended testis, Seminoma, Exclusive intertubular growth